Divided the genus Tachycines Adelung (Orthoptera, Rhaphidophoridae: Aemodogryllinae; Aemodogryllini) from China - Qin, Yanyan; Wang, Hanqiang; Liu, Xianwei; Li, Kai (Zootaxa, 2018)
This work involves revised analysis of Karny’s classification system in 1934 of the genus Tachycines Adelung, 1902 including the two subgenera: Tachycines (Tachycines) s. str. Adelung, 1902 and Tachycines (Gymnaeta) Adelung, 1902. We also describe 11 new species of Tachycines (Tachycines): Tachycines (Tachycines) karnyi sp. nov., Tachycines (Tachycines) maximus sp. nov., Tachycines (Tachycines) multispinosus sp. nov., Tachycines (Tachycines) xiai sp. nov., Tachycines (Tachycines) bilobatus sp. nov., Tachycines (Tachycines) trilobatus sp. nov., Tachycines (Tachycines) transversus sp. nov., Tachycines (Tachycines) incisus sp. nov., Tachycines (Tachycines) yanlingensis sp. nov., Tachycines (Tachycines) baiyunjianensis sp. nov., Tachycines (Tachycines) sichuanensis sp. nov.. A key to the subgenera of Tachycines Adelung, 1902 and a key to the species of Tachycines (Tachycines) are provided.